Civil service systems in East and Southeast Asia - Park, Chong-Min; Han, Yousueng; Chang, Yongjin (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book compares contemporary civil service systems across East and Southeast Asia, a dynamic region of greater diversity in local administrative tradition, imported models of modern administration, and the character of prevailing political institutions. Featuring chapters on Japan, South Korea, Taiwan, Singapore, Hong Kong, Vietnam, Indonesia, Thailand, Malaysia, and the Philippines, this book provides a detailed analysis of key aspects of the civil service system, including centralization, recruitment, classification, openness of positions, performance assessment, promotion, training, and senior civil service. It distinguishes four modes of public employment, namely, bureaucratization, professionalization, politicization, and marketization, to develop a conceptual framework for comparing the civil service system at the operational level. The region's contemporary civil service systems appear to be hybrid systems that combine, at varying degree, these modes of public employment, responding to administrative reform pressures. The patterns of public employment across East and Southeast Asia reflect local administrative traditions, imported Western models of administration, and the relative timing of democratization and bureaucratization. With contributions from leading local experts across the region, this book will be invaluable to students, scholars, and practitioners interested in Asian public administration, especially civil service systems"--
Keywords: Civil service -- East Asia; Civil service -- Southeast Asia; Public administration -- East Asia; Public administration -- Southeast Asia; POLITICAL SCIENCE / Public Affairs & Administration